Parenting Conflicts in Young Adults with Adverse Childhood Experiences: Family Conflict Theory Analysis - Diah Ayu Septiyani; Ika Febrian Kristiana (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
This study examined childhood trauma in young adults by parental conflict. The young adult phase is a very important transition in which from adolescence to independence as an adult related to traumatic experiences resulting from past parenting patterns. Researchers using family conflict theory aim to explore and analysis the contribution of adverse childhood experiences to parenting conflict in young adults. Using systematic literature review and the PRISMA method by reviewing research articles published from 2015-2025, the keywords used were "(Adverse childhood experiences OR ACE OR Child Abuse Or Childhood Trauma)” AND “(Family conflict OR family conflict OR conflict within the family OR Conflict between parents of children)" from several databases including Scopus, EBSCOhost, Science Direct, SpringerLink and PubMed. This study also emphasizes the negative impact of trauma and conflict in the family as analyzed from the theory of family conflict. The results reviewed from four articles show family conflict theory explains that ACE triggers intergenerational parenting conflict through role and communication imbalances, emphasizing the importance of holistic interventions to break the cycle of trauma and build healthy family dynamics.